Seed exchange networks for agrobiodiversity conservation. A review - Pautasso, M.; Aistara, G.; Barnaud, Adéline; Caillon, S.; Clouvel, P.; Coomes, O.T.; Deletre, M.; Demeulenaere, E.; Santis, P. de; Doring, T.; Eloy, L.; Emperaire, L.; et al. (Springer, 2013)
The circulation of seed among farmers is central to agrobiodiversity conservation and dynamics. Agrobiodiversity, the diversity of agricultural systems from genes to varieties and crop species, from farming methods to landscape composition, is part of humanitys cultural heritage. Whereas agrobiodiversity conservation has received much attention from researchers and policy makers over the last decades, the methods available to study the role of seed exchange networks in preserving crop biodiversity have only recently begun to be considered. In this overview, we present key concepts, methods, and challenges to better understand seed exchange networks so as to improve the chances that traditional crop varieties (landraces) will be preserved and used sustainably around the world. The available literature suggests that there is insufficient knowledge about the social, cultural, and methodological dimensions of environmental change, including how seed exchange networks will cope with changes in climates, socio-economic factors, and family structures that have supported seed exchange systems to date. Methods available to study the role of seed exchange networks in the preservation and adaptation of crop specific and genetic diversity range from meta-analysis to modelling, from participatory approaches to the development of bio-indicators, from genetic to biogeographical studies, from anthropological and ethnographic research to the use of network theory. We advocate a diversity of approaches, so as to foster the creation of robust and policy-relevant knowledge. Open challenges in the study of the role of seed exchange networks in biodiversity conservation include the development of methods to (i) enhance farmers participation to decision-making in agro-ecosystems, (ii) integrate ex situ and in situ approaches, (iii) achieve interdisciplinary research collaboration between social and natural scientists, and (iv) use network analysis as a conceptual framework to bridge boundaries among researchers, farmers and policy makers, as well as other stakeholders.